2007
DOI: 10.1102/1470-7330.2007.0027
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT and hepatic radiation injury in esophageal cancer patients

Abstract: This paper evaluates the imaging appearance of radiation injury in the liver on positron emission tomography (PET)/computed tomography (CT) in patients with distal esophageal cancer who underwent pre-operative chemoradiation therapy. Twenty-six patients with distal esophageal cancer who received chemoradiotherapy before esophagectomy were included. All patients had baseline and follow-up PET/CT. Fluorodeoxyglucose (FDG) uptake in both left and right lobes of the liver was evaluated. CT findings suggesting radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 28 publications
5
49
0
Order By: Relevance
“…In parallel with this therapeutic advance, PET/CT has become increasingly used as valuable imaging tools, both for baseline staging and for evaluation of treatment response [714]. However, it is known that radiation-induced liver disease can be a complication of radiotherapy, and one small study (n = 26) suggested that it may cause potentially confusing increased FDG avidity in the liver [13]. Therefore, we undertook this study to determine the frequency and appearance of radiation-induced liver disease on PET/CT in patients undergoing serial imaging during neoadjuvant chemoradiation of distal esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with this therapeutic advance, PET/CT has become increasingly used as valuable imaging tools, both for baseline staging and for evaluation of treatment response [714]. However, it is known that radiation-induced liver disease can be a complication of radiotherapy, and one small study (n = 26) suggested that it may cause potentially confusing increased FDG avidity in the liver [13]. Therefore, we undertook this study to determine the frequency and appearance of radiation-induced liver disease on PET/CT in patients undergoing serial imaging during neoadjuvant chemoradiation of distal esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…9 Preoperative whole-body PET/CT is frequently used to evaluate radiation treatment response and exclude metastases. Radiation-induced liver injury may be detected by PET/CT within 2 to 6 weeks after completion of radiation therapy, as a focal area of increased FDG uptake (>50% over baseline) in the liver adjacent to the irradiated field with associated decreased attenuation on CT. 10 As in our case, accompanying abnormalities in Alk Phos may be present in otherwise asymptomatic patients. 10 The FDG avidity is thought to represent uptake in active leukocytes because of inflammatory response in the liver.…”
Section: Imaging Features Of Radiation-induced Liver Injurymentioning
confidence: 70%
“…Radiation-induced liver injury may be detected by PET/CT within 2 to 6 weeks after completion of radiation therapy, as a focal area of increased FDG uptake (>50% over baseline) in the liver adjacent to the irradiated field with associated decreased attenuation on CT. 10 As in our case, accompanying abnormalities in Alk Phos may be present in otherwise asymptomatic patients. 10 The FDG avidity is thought to represent uptake in active leukocytes because of inflammatory response in the liver. 11 A recent study found that 9% of patients developed new FDG uptake in the liver during neoadjuvant chemoradiation for distal esophageal carcinoma, of which 8% proved to be radiation-induced liver injury rather than metastases.…”
Section: Imaging Features Of Radiation-induced Liver Injurymentioning
confidence: 70%
“…Abnormal FDG uptake in the irradiated liver was found in 19 % of the patients (Fig. 23) (Iyer et al 2007). However, CT images demonstrated atrophy and density changes of irradiated liver in 58 % of the same patients group.…”
Section: Mrimentioning
confidence: 94%